2009
DOI: 10.1007/s00239-008-9188-z
|View full text |Cite
|
Sign up to set email alerts
|

Internal Repetition and Intraindividual Variation in the rDNA ITS1 of the Anopheles punctulatus Group (Diptera: Culicidae): Multiple Units and Rates of Turnover

Abstract: The rapid divergence of repetitive sequences makes them desirable markers for phylogenetic studies of closely related groups, provided that a high level of sequence homogeneity has been maintained within species. Intraspecific polymorphisms are found in an increasing number of studies now, and this highlights the need to determine why these occur. In this study we examined intraindividual variation present in the first ribosomal internal transcribed spacer (ITS1) from a group of cryptic mosquito species. Indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 49 publications
(61 reference statements)
1
31
0
2
Order By: Relevance
“…However, it appears there is a limit to this process, given that An. annulipes has a larger ITS2 region (601 bp, Bower et al 2009) but does not assemble into a single contig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it appears there is a limit to this process, given that An. annulipes has a larger ITS2 region (601 bp, Bower et al 2009) but does not assemble into a single contig.…”
Section: Resultsmentioning
confidence: 99%
“…punctulatus species group species considered to be the most significant vectors of malaria in PNG. 59,[64][65][66][67] Additionally, some polymorphisms within species, namely An. farauti s.s. and An.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a high GC ratio would stabilize dsDNA in both PCR products and intramolecular secondary structures, and could inhibit the PCR. Moreover Bower et al (2009) reported that the GC ratio ITS2 from An. punctulatus group varied between 64-71.3%.…”
Section: Resultsmentioning
confidence: 99%